Komunikasi Interpersonal Dalam Kesehatan Mental Followers Akun Instagram @Ibunda.Id - Aryshinta, Aura Aditra; Ayuningtyas, Fitria; Muqsith, Munadhil Abdul (Communicology: Jurnal Ilmu Komunikasi, 2023)
ABSTRACT Social media is one of the most popular media in Indonesia, including Instagram. Instagram is a social media platform that allows users to upload content such as texts, photos, and videos on the feed, stories, and reels Instagram. Instagram users can communicate with other individuals or organizations by giving likes and comments on photos and videos. However, the messages received can contain something positive or negative that can affect mental health. Mental health disorders can cause uncomfortable feelings such as feeling guilty, anxious, afraid, or comparing oneself to the content displayed on social media. This article explains the results of research on the phenomenon of increasing mental health problems in the productive age group. The effort made to address this issue is by providing information and communication about mental health on social media, including Instagram. This research aims to measure interpersonal communication related to mental health on the Instagram platform using the encoding-decoding theory. The method used is qualitative descriptive by conducting interviews with 6 active followers of the @ibunda.id Instagram account. The results show that there is a difference in how followers interpret the information and communication presented in the content on the account, some followers accept all the information presented, and other followers have a different opinion about the meaning of the information presented. Keywords: Encoding-Decoding Theory; Interpersonal Communication; Mental Health ABSTRAK Media sosial adalah salah satu media yang sedang populer di Indonesia, termasuk Instagram. Instagram adalah media sosial yang memungkinkan pengguna untuk mengunggah konten-konten berupa teks, foto, dan video di feed, stories dan reels Instagram. Pengguna Instagram dapat berkomunikasi dengan individu atau organisasi lain melalui memberikan like dan komentar pada foto dan video. Namun, pesan yang diterima dapat berisi sesuatu yang positif atau negatif yang dapat mempengaruhi kesehatan mental. Kesehatan mental yang terganggu dapat menyebabkan perasaan tidak nyaman seperti merasa bersalah, cemas, takut, atau membandingkan diri sendiri dengan konten yang ditampilkan di media sosial. Artikel ini menjelaskan hasil penelitian tentang fenomena meningkatnya masalah kesehatan mental pada kelompok usia produktif. Upaya yang dilakukan untuk menangani masalah ini adalah dengan memberikan informasi dan komunikasi tentang kesehatan mental di media sosial, termasuk Instagram. Penelitian ini bertujuan untuk mengukur komunikasi interpersonal terkait kesehatan mental di platform Instagram menggunakan teori encoding-decoding. Metode yang digunakan adalah kualitatif deskriptif dengan melakukan wawancara terhadap 6 orang followers aktif akun Instagram @ibunda.id. Hasilnya menunjukkan bahwa ada perbedaan dalam cara followers menafsirkan informasi dan komunikasi yang disampaikan konten-konten di akun tersebut, ada followers yang menerima semua informasi yang disajikan, dan followers lainnya memiliki pendapat yang berbeda tentang makna informasi yang disampaikan. Kata kunci: Komunikasi Interpersonal; Kesehatan Mental; Teori Encoding-Decoding